2008
DOI: 10.1002/art.24002
|View full text |Cite
|
Sign up to set email alerts
|

Attributable risk of carpal tunnel syndrome according to industry and occupation in a general population

Abstract: Objective. An epidemiologic surveillance network for carpal tunnel syndrome (CTS) was set up in the general population of a French region to assess the proportion of CTS cases attributable to work in high-risk industries and occupations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 24 publications
3
37
1
4
Order By: Relevance
“…These electrophysiological and clinical findings suggest extensive fascicular involvement within the median nerve in contrast to idiopathic CTS. [1][2][3] There were statistically significant positive correlations between the clinical stages of the patients and the age, working duration and duration of symptoms in our study. A statistically significant positive correlation was also present between the neurophysiologic grades of the patients and the duration of symptoms in our study (Table II).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These electrophysiological and clinical findings suggest extensive fascicular involvement within the median nerve in contrast to idiopathic CTS. [1][2][3] There were statistically significant positive correlations between the clinical stages of the patients and the age, working duration and duration of symptoms in our study. A statistically significant positive correlation was also present between the neurophysiologic grades of the patients and the duration of symptoms in our study (Table II).…”
Section: Discussionsupporting
confidence: 64%
“…Carpal tunnel syndrome is shown to have a higher incidence rate in employed patients than in unemployed persons. [2,3,7,[16][17][18][19] It has been shown that occupational exposure to excess vibration, increased hand force and repetition increases the risk of developing CTS in a meta-analysis investigating the relationship between CTS and occupation. [20] Lengthy exposure to high repetitive hand and wrist movements, high range wrist action, constant extreme wrist position, using handheld vibrating tools, work involving frozen food and availability of protection have been shown to be the key occupational points to consider in determining work liability for CTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggest that calculating attributable fractions to estimate excess risk is more meaningful [Palmer et al, 2008;Roquelaure et al, 2008]. We plan to calculate attributable fractions in future analyses.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…KTS için risk faktörleri kadın cinsiyet, ileri yaş, obezite, yüksek vücut kitle indeksi (VKİ), gebelik, diyabetes mellitus, renal hastalıklar, hipotiroidi, amiloidoz, akromegali ve konnektif doku hastalıklarıdır (3). Ayrıca tekrarlayıcı el hareketleri ile ilişkili mesleki faktörler de son yıllarda göze çarpan önemli risk faktörleridir (4). Klinik olarak ilk üç parmakta uyuşma, bilek ile ön kolda ağrı ve güçsüzlük ayrıca tenar bölgede atrofi gibi yakınmalar görülür.…”
Section: Introductionunclassified